Distinct Modulation of Spontaneous and GABA-Evoked Gating by Flurazepam Shapes Cross-Talk Between Agonist-Free and Liganded GABAA Receptor Activity - Jatczak-Śliwa, Magdalena; Terejko, Katarzyna; Brodzki, Marek; Michałowski, Michał A.; Czyzewska, Marta M.; Nowicka, Joanna M.; Andrzejczak, Anna; Srinivasan, Rakenduvadhana; Mozrzymas, Jerzy W. (Frontiers in Cellular Neuroscience, 2018)
GABAA receptors (GABAARs) play a crucial inhibitory role in the CNS. Benzodiazepines (BDZs) are positive modulators of specific subtypes of GABAARs but the underlying mechanism remains obscure. Early studies demonstrated major impact of BDZs on binding whereas more recent investigations indicated gating but it is unclear which transitions are affected. Moreover, upregulation of GABAAR spontaneous activity by BDZs indicates their impact on receptor gating but the underlying mechanisms remain unknown. Herein, we investigated a BDZ (flurazepam) effect on the spontaneous and GABA-induced activity for wild-type (WT, α1β2γ2) and mutated (at the orthosteric binding site α1F64) GABAARs. Surprisingly, in spite of localization at the binding site, these mutations increased the spontaneous activity. Flurazepam (FLU) upregulated this activity for mutants and WT receptors to a similar extent by affecting opening/closing transitions. Spontaneous activity affected GABA-evoked currents which is manifested as an overshoot after agonist removal which depended on modulation by BDZs. We explain the mechanism of this phenomenon as a cross-desensitization of ligand-activated and spontaneously active receptors. Moreover, due to spontaneous activity, FLU-pretreatment and co-application (agonist + FLU) protocols yielded distinct results. We provide also the first evidence that GABAAR may enter the desensitized state in the absence of GABA in a FLU-dependent manner. Based on our data and model simulations, we propose that FLU affects agonist-induced gating by modifying primarily preactivation and desensitization. We conclude that the mechanisms of modulation of spontaneous and ligand-activated GABAAR activity concerns gating but distinct transitions are affected in spontaneous and agonist-evoked activity.